Usulan pengembangan fasilitas dan perangkat kendaraan siaran langsung (OB VAN) (Studi kasus di LPPL Radio Gemilang FM Magelang) - Affan Rifai; Imam Djati Widodo; Ali Parkhan (Teknoin, 2017)
OB (Outside Broadcasting) Van Radio Gemilang FM Magelang is a vehicle that has studio facilities and transmitting equipment as a studio and broadcast radio transmitters in general in the form of mini and specific functions. From various user inputs such as broadcast division, operator and technical part there are development opportunities that can be done to further improve the quality of facilities and devices according to the needs of coverage and technology activities in the future. This study involved 30 respondents who are competent in operating OB Van equipment. The method used in this development proposal using the measurement of technique parameters with QFD method up to level 2, there are 17 quality variables that are based on 8 Quality Dimension Garvin. From the results of research conducted there are 10 technical respond that can be done, with the most important development priority is software development and audio codec device to reduce digital audio transfer rate transfer with weight 297,7 and internet connection quality with weight 256,8.